Variation morphologique et concept d’espèce en paléoanthropologie : l’exemple d’Australopithecus en Afrique australe - Amélie Beaudet (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Interpreting and understanding morphological variation within the fossil hominin record represent one of the major challenges in palaeoanthropology. The lack of a consensual definition of the species concept in palaeontology, together with the fragmentary nature of the fossil record, greatly impact our understanding of the fossil hominin taxonomic diversity. Historical debates around the fossil remains attributed to Australopithecus in southern Africa is an emblematic example of the influence of those questions on our understanding of human evolution. Since the earliest discoveries, scientific papers have been reporting a high degree of morphological variation within this assemblage. Since then, subsequent excavations have confirmed this outstanding variation. While some authors interpret this variation as a proof of the presence of more than one Australopithecus species, others explore alternative hypotheses to tentatively explain this variation. Far from being anecdotical, this presumed taxonomic diversity within the genus Australopithecus would substantially modify our grasp of speciation processes within Plio-Pleistocene hominins. In this synthesis, I describe the factors that play a role in morphological variation before going through the history of discoveries and studies that raised concerns and questions about the diversity within southern African Australopithecus and investigating the factors that may explain this conundrum.